اثر الانفتاح التجاري في تعزيز وتنمية القطاع المالي: البلدان العربية انموذجا - قيس ناظم غزال; بشار احمد العراقي; حلا سامي خضير الياسين (PROSPECTIVE RESEARCHES, 2023)
The aim of this research is to provide a clear holistic picture of theoretical frameworks and empirical studies that have attempted to analyze and explain the mechanism and channels of impact that high levels of Trade Openness can enhance Promoting and Developing the Financial Sector. In addition, building an objective Empirical model that can clarify the nature, value, and direction of this effect. The methodology of Pooled Regression Model (PRM), Fixed Effect Model (FEM) and Random Effect Model (REM) based on Balanced Panel Data were used for a group of Arab countries for the period (1990-2018). The results revealed a positive effect of statistically significant Trade Openness (TO) on the three financial development indicators represented by the Bank Credit to the Private Sector as percent of GDP (BC), Liquid Liabilities as percent of GDP (LL), and Bank Assets as percent of GDP (BA), for a group Arab country during the study period. Reflecting an additional support for theoretical frameworks and empirical studies for the positive role that trade openness exercises in Aziz and the hope of the financial sector in its current form, which pushes economic, financial and political decision-makers towards the possibility of adopting and formulating policies that support Trade Openness and stimulate its diversity and expansion.